2014
DOI: 10.1111/ppa.12217
|View full text |Cite
|
Sign up to set email alerts
|

Thermal requirements and population dynamics of root‐knot nematodes on cucumber and yield losses under protected cultivation

Abstract: Several studies were carried out to determine (i) thermal requirements for development, egg production and emergence of juveniles, and completion of the life cycle of Meloidogyne incognita and Meloidogyne javanica on cucumber, (ii) the maximum multiplication rate and the equilibrium density of root-knot nematodes on cucumber and yield losses in pot and plastic greenhouse experiments, and (iii) the relationships between relative leaf chlorophyll content (RLCC) and relative cucumber dry top weight biomass (RDTWB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 26 publications
6
55
0
4
Order By: Relevance
“…As a result, nematode-induced changes in both plant water and nutrient status led to a decrease in net photosynthetic rate. Therefore, in agreement with previous studies, nematode infection caused a reduction in leaf chlorophyll content (Audebert et al 2000 ;Ahmed et al 2009 ;Khan and Haque 2011 ;Giné et al 2014 ;López-Gómez et al 2015 ) as well as in photosynthetic activity (Loveys and Bird 1973 ;Melakeberhan et al 1985 ) as suggested by the negative relationship between Pi and net photosynthetic rate. In addition, for both grafted or ungrafted cucumber plants, relative changes in yield were also related to the relative variation in both R / [R x R ] and net photosynthetic rate, confirming previous results in which relative dry top weight of cucumber or zucchinisquash biomass (López-Gómez et al 2015 ) was related to relative leaf chlorophyll content.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…As a result, nematode-induced changes in both plant water and nutrient status led to a decrease in net photosynthetic rate. Therefore, in agreement with previous studies, nematode infection caused a reduction in leaf chlorophyll content (Audebert et al 2000 ;Ahmed et al 2009 ;Khan and Haque 2011 ;Giné et al 2014 ;López-Gómez et al 2015 ) as well as in photosynthetic activity (Loveys and Bird 1973 ;Melakeberhan et al 1985 ) as suggested by the negative relationship between Pi and net photosynthetic rate. In addition, for both grafted or ungrafted cucumber plants, relative changes in yield were also related to the relative variation in both R / [R x R ] and net photosynthetic rate, confirming previous results in which relative dry top weight of cucumber or zucchinisquash biomass (López-Gómez et al 2015 ) was related to relative leaf chlorophyll content.…”
Section: Discussionsupporting
confidence: 78%
“…The results of this study show that values of a and E of M. incognita on ungrafted cucumber cv. Dasher II cropped in spring-summer (April to July) were lower than those reported by Giné et al ( 2014 ) when cucumber was cropped in summer-autumn (July to November). Similar results were reported for M. incognita on zucchini-squash ) and for M. artiellia on chickpea (Di Vito and Greco 1988 ).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The leaf chlorophyll content (LCC) has been used as an indicator for evaluation of nematode damage (Loveys & Bird, 1973;Melakeberhan et al, 1985;Giné et al, 2014;López-Gómez et al, 2015) due to the strong correlation between LCC and the nitrogen content of the plant (Gholizadeh et al, 2009;Pôrto et al, 2011). Changes in LCC may be detected before the appearance of disease symptoms (Wagner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%